COMBAT STRESS AND RESULTS OF ITS EMPIRICAL STUDY - Blinov, Oleg (PSYCHOLOGICAL JOURNAL, 2018)
The article deals with the phenomenology of combat stress and the conditions for its emergence. The actuality of the problem of combat stress and post-traumatic stress disorder of military men is shown. The analysis of opinions of experts about the features and possible levels of its manifestations has been carried out. The results of research on combat stress and post-traumatic stress disorder are presented. The reasons and peculiarities of the manifestations of the emotional experiences of military men as a result of traumatic stress are defined and considered with the help of the posttraumatic stress disorder screening questionnaire (PTSD SQ), the questionnaire of combat stress by O. A. Blinov (СSQ). The correlation relationships between the indicators of combat stress of the questionnaires were established. As a result of empirical studies, it has been determined that 8% of military men who participated in combat operations need an in-depth examination of the probability of post-traumatic stress disorder, and it was detected in 19% of them. Among the wounded combatants 13% require additional examination on the subject of post-traumatic stress disorder, and it was detected in 46% of military men.